Avaliação do potencial neuroprotetor do ômega-3 e do ácido fólico, isolados ou em combinação, em modelo animal de transtorno do espectro autista - Oliveira, Juliana (2018)
Gestational period is a phase in wich nutrional requiriments are elevated, due the pregnant phisiological adjustments and fetal growth nutrition demands. Genetic factors, infections, inflammations as well as maternal bad nutrition during gestational period and postnatal life may promote cellular disfunctions and contribute to development of psychiatric and neurologic disorder, as Autistc Spectrum Disorder (ASD). Considering that ASD is related to neurodevelopment alterations caused by inflammatory process, therapeutic approaches such as ω3 and folic acid supplementation, alone or in combination, wether in postnatal or in periconcepcional period, may represent nonpharmacologic alternative, associated to prevention. Objective: To evaluate the effects of administration of ω3 and folic acid, alone or in combination, in neuroprotection of rats submitted to ASD experimental model. Methods: The supplementation period comprehended a 15 days adaptation stage before mating and it was extended through gestation and lactation stages, that is to say, until postnatal day (PND) 21 puppies days. Behavioral tests have been conducted in PND45 and PND 52, posteriorly, animals were submitted to painless assisted death protocol and structures of interest (prefrontal cortex, hippocampus and cerebellum) were isolated and storaged to oxidative lipid damage level and protein oxidative damage analisys. Results: Maternal supplementation with ω-3 and pholic acid, alone or in combination, were capable of reversing parameters of stereotypy and social interaction, mainly in male animals, and memory improvement in female memory of habituation. Same protocols of supplementation reverse oxidative damage in lipid and proteins caused by lipopolysaccharide (LPS) administrated prenatally. Conclusion: Results suggests the neuroprotector role of ω-3 and folic acid, alone or in combination, both in male and in female animals, submitted to preclinical model of TEA.